Exercise-triggered cardiac remodeling: AKIP1 as a novel mediator of physiological hypertrophy - Jiahui Li; Jianghao Zhan; Yinuo Liu; Maorui Han; Jie Qi; Jun Zhang (Advanced Exercise and Health Science, 2025)
A kinase interacting protein 1 (AKIP1) is a signal transduction junction protein that promotes physiological hypertrophy. This study aimed to investigate whether exercise induces AKIP1 to promote physiological cardiac hypertrophy and the effects for signaling pathways. 24 6-week-old C57BL/6 N male mice were randomly divided into quiet control group (CON group), exercise group (EX group), and interference-expressing AKIP1 adeno-associated virus in vivo injection+exercise group (shAAV-AKIP1 +EX group) for 10 weeks in running exercise. The cardiac were examined by ultrasound, electrocardiography, HE staining and detection of AKIP1 mRNA and protein expression. The mRNA expression of myocardial pathological markers (ANP, BNP, α-actin, α-MHC, and β-MHC), physiological marker (SERCA2α), PI3K (p110α), and mTORC1 were also determined. The results showed that compared with CON group, the left ventricular cell volume was significantly increased, the myocardial fibers were thickened and more closely arranged in EX group. Meanwhile, there was no pathological myocardial fibrosis. The ventricular internal diameters, HW/TL ratio, LVMI, EF, FS and SERCA2α mRNA expression was significantly increased in EX group as in contrast to the CON group (P < 0.05). However, EF, FS as well as SERCA2α mRNA expression were significantly lower in shAAV-AKIP1 +EX group compared with the EX group (P < 0.05), whereas cardiac indexes were not significantly affected (P > 0.05). Both AKIP1 mRNA and protein levels expression were markedly higher in EX group than CON group (P < 0.01), while notably downregulated in shAAV-AKIP1 +EX group compared to the CON group and EX group (P < 0.01). The PI3K (p110α) and mTORC1 mRNA expression in EX group were significantly higher than CON group, whereas they were significantly decreased in the shAAV-AKIP1 +EX group compared with the CON and EX groups (P < 0.01). Our results identify AKIP1 as a novel mediator of physiological hypertrophy, also highlight that the formation of exercise cardiac hypertrophy may be facilitated by AKIP1 through activation of the PI3K/AKT/mTOR signaling pathway.